Stiffness- and relaxation-based quantitation of radial left ventricular oscillations: elucidation of regional diastolic function mechanisms - Riordan, Matt M.; Kovács, Sándor J. (Journal of applied physiology (1985), 2007)
Traditionally, global and longitudinal (i.e., regional) left ventricular (LV) diastolic function (DF) assessment has utilized features of transmitral Doppler E and A waves or Doppler tissue imaging (DTI)-derived mitral annular E′ and A′ waves, respectively. Quantitation of regional DF has included M-mode echocardiography-based approaches and strain and strain rate imaging (in selected imaging planes), while analysis of mitral annular “oscillations” has recently provided a new window into longitudinal (long-axis) function. The remaining major spatial degree of kinematic freedom during diastole, radial (short-axis) motion, has not been fully characterized, nor has it been exploited for its potential to provide radial LV stiffness ( k rad ) and relaxation/damping ( c rad ) indexes. Prior characterization of regional (longitudinal) DF used only annular E′- and A′-wave peak velocities or, alternatively, myocardial strain and strain rate. By kinematically modeling short-axis tissue motion as damped radial oscillation, we present a novel method of estimating k rad and c rad during early filling. As required by the (near) constant-volume property of the heart and tissue/blood incompressibility, in subjects ( n = 10) with normal DF, we show that oscillation duration-determined longitudinal ( k long and c long ) and radial ( k long and c rad ) parameters are highly correlated ( R = 0.69 and 0.92, respectively). Selected examples of diabetic and LV hypertrophic subjects yield radial ( k long and c rad ) parameters that differ substantially from controls. Results underscore the utility of the incompressibility-based causal relation between DTI-determined mitral annular long-axis (longitudinal mode) and short-axis (radial mode) oscillations in healthy subjects. Selected pathological examples provide mechanistic insight and illustrate the value and potential role of regional (longitudinal and radial) DF indexes in fully characterizing normal vs. impaired DF states.